POLITIK HUKUM FUNGSI BANK SEBAGAI AGEN REKSADANA DI PASAR MODAL - Setiadi, Tri (Universitas Wiralodra, 2019)
The politics of law in the field of Indonesian piracy associated with the function of banks as mutual fund agents in the capital market in the era of free trade must be able to accommodate the main objectives of regulating banking institutions, namely the stability of the banking institutions as described above. The involvement of banks as mutual fund agents must pay attention to risk management because mutual funds are investment products that have risks and can affect the relationship between the bank and its customers and have a large impact on public trust in the bank. The legal policy must be stated in the product of legislation that regulates banking and capital market investment in this case the involvement of banks in mutual funds. The law must be a guide in the relationship between banking institutions and society.